Synthesis and characterization of a plant growth regulator based silver nanoparticles for the ultrasensitive detection of environmentally toxic Hg2+ ions in tap water. (13th September 2021) - Ahmed, Farid; Ali, Imdad; Saad Ali, Heyam; Yasmeen, Saira; Ullah, Shafi; Burki, Samiullah; Adil, Muhammad; Nisar, Jan; Shah, Muhammad Raza
Abstract : Herein, we report the synthesis and characterization of a plant growth regulator based silver nanoparticles and its application as a sensor for the ultrasensitive detection of toxic metal ions (Hg 2+ ) in tapwater. Abstract : Herein, we report the synthesis and characterization of a plant growth regulator based silver nanoparticles for use as a sensor for the ultrasensitive detection of toxic metal ions (Hg 2+ ) in tapwater. Kinetin-based nanoparticles (Kin–AgNPs) were synthesized by a chemical reduction method and characterized using ultraviolet (UV)-visible, atomic force microscopy (AFM), Zetasizer analysis, and Fourier-transform infrared (FTIR) spectroscopic techniques. The average size of the NPs was found to be in the range of 40–60 nm. The Kin–AgNPs were found to be extremely stable at high temperatures, high electrolyte concentrations, and over a wide pH range. The UV-visible spectroscopy was used to investigate the sensing ability of the Kin–AgNPs towards metal cations. The addition of Hg 2+ produces a significant reduction in the absorption intensity of the Kin–AgNPs. The Kin–AgNPs were found to be highly selective even in the presence of several other competing metal cations. A direct linear relationship between absorption intensity and Hg 2+ concentration was observed in the range of 0.01 μM to 100 μM, with an R 2 value of 0.98. The synthesized Kin–AgNP-based nanosensor detected Hg 2+ ions with a limit of detection of 6.6 nM. Moreover, the Kin–AgNPs were successfully used for the detection of mercury in laboratory tap water.